2003
DOI: 10.1002/bapi.200301660
|View full text |Cite
|
Sign up to set email alerts
|

Algen, Flechten, Moose und Farne auf Fassaden

Abstract: Die optische Beeinträchtigung von Fassaden und Außenbauteilen durch biologischen Aufwuchs wird zunehmend als wissenschaftliche und industrielle Thematik erkannt. Zahlreiche Autoren diskutieren mögliche Gegenmaßnahmen, während hinsichtlich der Zusammensetzung des Aufwuchses noch große Unsicherheit besteht. In einem interdisziplinären Projekt am Fraunhofer‐Institut für Bauphysik (IBP) werden derzeit zusätzlich zu den biologischen auch die chemisch‐physikalischen Vorgänge untersucht und dokumentiert, deren vorläu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 0 publications
0
9
0
2
Order By: Relevance
“…A valuable tool for ecophysilogic investigations are defined cultures. The collection of building relevant microorganisms, BRMO, established in the course of work on primary colonization of building surfaces, is providing a source of knowledge and documentation for building relevant algae and fungi [ 1 , 2 , 3 , 31 ].…”
Section: Algae Toxic To the Built Environment Or To Work Of Menmentioning
confidence: 99%
See 2 more Smart Citations
“…A valuable tool for ecophysilogic investigations are defined cultures. The collection of building relevant microorganisms, BRMO, established in the course of work on primary colonization of building surfaces, is providing a source of knowledge and documentation for building relevant algae and fungi [ 1 , 2 , 3 , 31 ].…”
Section: Algae Toxic To the Built Environment Or To Work Of Menmentioning
confidence: 99%
“…In recent studies on the initial growth on modern façades, an unexpected diversity was found with more than 70 species. On surfaces of insulated façades, eukaryotic algae, especially green algae prevail, mainly Trebouxiophyceae, supplemented by other algal taxa [ 1 , 2 , 3 ]. Substrates and habitats may be all exposed materials, masonry, concrete, metal posts and signs, varnished surfaces, plastic, glass, ceramics, wood, monuments and other works of art, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Výskumy v oblasti kolonizácie ETICS mikroorganizmami sú okrem zisťovania príčin orientované aj na hodnotenie významnosti kolonizácie. V tejto súvislosti, bol okrem taxonomického zaradenia identifikovaných druhov mikroorganizmov na fasáde, vytvorený návod pre vizuálne určenie kvantitatívneho zastúpenia mikroorganizmov na ETICS a určenie významnosti kolonizácie [2]. Vývoj kolonizácie mikroorganizmov pozorovali nemeckí vedci v období 5 rokov.…”
Section: Hodnotenie Technického Stavu Etics S Biokoróziouunclassified
“…The expected life of ETICS is 25-30 years (ETAG 2004) so this treatment should be repeated [2]. Studies in the field of ETICS colonization by microorganisms have been oriented to assess the significance of colonization [3][4]. The chemicals used for microorganisms´ elimination on the facades, either as bounded, encapsulated in pigments and plaster or loose, un-encapsulated agents, reducing their development and growth, containing mainly toxic heavy metal compounds, are based on the basis of active silver.…”
Section: Introductionmentioning
confidence: 99%